Identification and quantification of microplastics contamination in potato from Malang Raya, Indonesia - Hendroko Setyobudi, Roy; Anwar, Shazma; Iswahyudi, Iswahyudi; Husen, Syarif; Damat, Damat; Mel, Maizirwan; Thontowi, Djauhari Nur Subchi (EDP Sciences, 2024)
The presence of microplastics (MPs) in agricultural soil has the potential to contaminate plants and agricultural products with negative impacts on humans and living creatures. Therefore, identifying and quantifying MPs in potato farms is essential to evaluate. This study aims to estimate MPs pollutants in potato farms. This study found that potato farm components (potato seedlings, soil, organic fertilizer, potato, irrigation water and potato chips) had a total MPs content of 104 particles. The higher abundance of MPs 2.83 mL–1 was recorded in Pujon Kidul irrigation water and lower abundance of MPs 0.03 g–1 was noted in Potato chip – “OK” brand. Considering size of microplastic the maximum size of MPs 5.449 mm was calculated in Pujon Kidul irrigation water and minimum size of MPs 0.172 mm was noted in Pujon Kidul 3rd growing media. The colors of MPs identified are transparent, black, blue, red, yellow, and green. In addition, the MP's shape was 68.2 % of fibre, 26.9 % of filament, 3.8 % fragment, and 1.1 % of granules in potato farm components. The emerging pollutants must be addressed because microplastic degradation causes them to spread more widely, accumulating over tens to hundreds of years as a hidden danger